Design, Analysis and Testing of Monopole Antenna Deployment Mechanism for BIRDS-2 CubeSat Applications. (January 2019) - Zaki, S B M; Azami, M H; Yamauchi, T.; Kim, S; Masui, H; Cho, M
Abstract: This paper presents an approach to design a feasible and reliable monopole antennae deployment mechanism for CubeSat applications. Nano-satellite has faced problems in designing antennae deployment system due to space and deployment mechanism constraints. In BIRDS-2 CubeSat, the nichrome wire burning release mechanism was used when activated, it will be heated up and thermally cut through fishing line, allowing the two monopole antennas to be deployed on +Y board and at +Z axis direction of the satellite. These antennae involved amateur radio frequencies in UHF and VHF bands due to its low cost and high accessibility by the end users. The UHF frequency band was used for command uplink, mission, telemetry, and CW beacon downlink whilst the VHF frequency band was used specifically for APRS-DP/S&F-RDC mission for both uplink and downlink. In order to achieve the effectiveness of the BIRDS-2 CubeSat communication system agreed with the link budget estimation, the dimensions of antennae on the CubeSat structure depend on the required gain and operating frequency. The paper discusses detailed results of mechanical and electrical interfaces of the two monopole antennas deployment mechanism with the satellite body and the nichrome wire burning release mechanism analysis. The tests results of the mechanism were analyzed particularly on the deployment time and the nichrome wire temperature differences.